MANAJEMEN PENYEIMBANG BEBAN DENGAN METODE LEAST CONNECTION PADA DIREKTORAT JENDERAL BEA DAN CUKAI - Atik Budi Paryanti; Ketut Apriana (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2018)
Information technology needs in the present are unavoidable, this applies also to the institution of the Directorate General of Customs and Excise, where the need for application and automation of business processes is absolutely necessary to support the duties and functions of the Directorate General of Customs and Excise. The number of applications that currently exist at the Directorate General of Customs and Excise are 60 applications with a number of users of approximately 15,000 users. The large number of application users can result in high server workloads both on the application server and database server, therefore a server workload balancing mechanism (load balancing) is needed. Currently the Directorate General of Customs and Excise has implemented load balancing technology using the F5 BIG-IP device. The device is capable of dividing the load of server work with several methods, but currently the most commonly used methods are least connection and round robin. The least connection method is a method that divides the load based on the number of connections on the server, while the round robin method, sharing load alternately. With the load balancer using the scheduling method is expected to be able to flatten the workload of the web server and accelerate the response time and throughput to the performance of the web server.